2005
DOI: 10.1517/14740338.5.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of infliximab in the course of treatment of Crohn’s disease

Abstract: Infliximab is a monoclonal antibody directed against the pro-inflammatory mediator TNF-alpha, which was approved in the US in 1998 for treatment-resistant Crohn's disease. Since that time, the indications have dramatically expanded to include rheumatoid arthritis, ankylosing spondylitis, psoriasis and most recently, active ulcerative colitis. Although the safety profile in the initial studies was quite favourable, subsequent studies have shown that a small percentage of patients reported severe side effects, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 87 publications
0
14
0
2
Order By: Relevance
“…Considering the function of TNF-alpha as a potent inflammatory mediator, one would expect that if this compound is blocked, there could be a potential risk for increased infection as shown in multiple studies. 23,24 Therefore, our finding of an increased incidence of sepsis and abscess after surgery is not surprising. It is also conceivable that the immunosuppressive effects of IFX may last well beyond the time when IFX is cleared from the body.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Considering the function of TNF-alpha as a potent inflammatory mediator, one would expect that if this compound is blocked, there could be a potential risk for increased infection as shown in multiple studies. 23,24 Therefore, our finding of an increased incidence of sepsis and abscess after surgery is not surprising. It is also conceivable that the immunosuppressive effects of IFX may last well beyond the time when IFX is cleared from the body.…”
Section: Discussionmentioning
confidence: 63%
“…14,15 There is a paucity of data on perioperative outcomes for CD patients on IFX undergoing surgery. Two previous studies 22, 23 reported outcomes in a small heterogeneous group of patients on the medication at variable time intervals before and after surgery. Since the complexity of surgery in CD patients may be variable and may, in itself, influence outcomes, we evaluated 30-day perioperative outcomes for CD patients who received IFX at any time within 3 months prior to undergoing ileocolonic resection.…”
Section: Introductionmentioning
confidence: 99%
“…Such strategy would have a number of obvious benefits compared to a standard prophylactic strategy [8][9][10]24]. Published data [5,6] do not clarify whether such strategy is truly effective [7].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, data related to the effect of infliximab therapy (rather than prophylaxis) for early endoscopic post surgical recurrence of CD are less consistent [5][6][7]. Such strategy would have clear cost and safety advantages over standard prophylaxis with the same drug [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Efficacy varies among patients, although nearly all improve to some extent. In a small percentage of patients, severe side effects, including pneumonia, tuberculosis, lymphoma, and hepatotoxicity, have been reported (31,32) . Therefore, several molecules have been studied to determine the additional therapeutic targets for arthritis.…”
Section: Discussionmentioning
confidence: 99%